Comparison of Activation Methods for 3D-Printed Electrodes for Microbial Electrochemical Technologies - Raúl M. Alonso; Isabel San Martín; Antonio Morán; Adrián Escapa (Applied Sciences, 2021)
Three-dimensional printing could provide flexibility in the design of a new generation of electrodes to be used in microbial electrochemical technologies (MET). In this work, we demonstrate the feasibility of using polylactic acid (PLA)/graphene—a common 3D-printing material—to build custom bioelectrodes. We also show that a suitable activation procedure is crucial to achieve an acceptable electrochemical performance (plain PLA/graphene bioanodes produce negligible amounts of current). Activation with acetone and dimethylformamide resulted in current densities similar to those typically observed in bioanodes built with more conventional materials (about 5 Am−2). In addition, the electrodes thus activated favored the proliferation of electroactive bacteria.